PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI TERHADAP KINERJA DOSEN DENGAN DISIPLIN SEBAGAI VARIABEL MEDIASI ( Studi Dosen Politeknik Ilmu Pelayaran Semarang ) - Arya Widiatmaja, 11.52.02.0037 (Students Journal of Economic and Management, 2013)
The purpose of this study is to examine the effect of professional competence and motivation on performance, moderated by the work discipline ofÂ lecturer in Polytechnic State of Semarang. Based on that conditions, the title of this study is